2009
DOI: 10.1021/nl900470p
|View full text |Cite
|
Sign up to set email alerts
|

β-Cyclodextrin-Modified CdSe/ZnS Quantum Dots for Sensing and Chiroselective Analysis

Abstract: Beta-cyclodextrin (beta-CD)-functionalized CdSe/ZnS quantum dots (QDs) are used for optical sensing and chiroselective sensing of different substrates using a fluorescence resonance energy transfer (FRET) or an electron transfer (ET) mechanisms. The FRET between the QDs and Rhodamine B incorporated in the beta-CD receptor sites is used for the competitive analysis of adamantanecarboxylic acid and of p-hydroxytoluene. Also, the dye-incorporated beta-CD-modified QDs are used for the chiroselective optical discri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
163
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 250 publications
(168 citation statements)
references
References 38 publications
(18 reference statements)
3
163
0
2
Order By: Relevance
“…The interdigitated bilayer structure of CTAB-TOPO-coated CdSe/ZnS QD, whose first layer was original surface ligands TOPO and the second layer was CTAB, made it a more sensitive and selective fluorescence probe than CdSe/ZnS QD to the quenchers [46]. Similar organic coated bilayer structures of water-soluble CdSe/ZnS QDs were also investigated by others as fluorescence quenching probes for selective detection and quantification of analytes like chloride anion [47], hypochlorite [48], heavy metal ions [27][28][29][30]49], nitroaromatic [50] and even chiral mixtures of enantiomers [51,52].…”
Section: Comparison Of Oil-soluble Qds and Water-soluble Ctab-coated Qdsmentioning
confidence: 99%
“…The interdigitated bilayer structure of CTAB-TOPO-coated CdSe/ZnS QD, whose first layer was original surface ligands TOPO and the second layer was CTAB, made it a more sensitive and selective fluorescence probe than CdSe/ZnS QD to the quenchers [46]. Similar organic coated bilayer structures of water-soluble CdSe/ZnS QDs were also investigated by others as fluorescence quenching probes for selective detection and quantification of analytes like chloride anion [47], hypochlorite [48], heavy metal ions [27][28][29][30]49], nitroaromatic [50] and even chiral mixtures of enantiomers [51,52].…”
Section: Comparison Of Oil-soluble Qds and Water-soluble Ctab-coated Qdsmentioning
confidence: 99%
“…It is worth noting that this approach has already been explored using small organic molecules instead of polymers. The QDs are in that case coated with amphiphilic phospholipids, 26 calixarenes 27,28 or cyclodextrins [29][30][31] to achieve the same goal. Besides, the silicacoating method [32][33][34][35][36] has also been used to tailor QDs for gaining solubilization and functionalization to conjugate with biofunctional molecules.…”
Section: Surface Stabilization Chemistrymentioning
confidence: 99%
“…CDs can be used as modified surface agent in the synthesis of nanostructure materials. Zhao and Chen have synthesized multi-petals ZnO nano-structure in the presence ofcyclodextrin and they found that if not using -CD in the preparation process, only larger rods could be obtained [10] and according to recent report, -Cyclodextrin ( -CD)-functionalized CdSe/ZnS quantum dots (QDs) apply for optical sensing [11]. To develop functional nanowebs, Uyar et al have synthesized cyclodextrin functionalized polyethylene oxide (PEO) nanofibers (PEO/CD) [12].…”
Section: Cyclodextrins (Cds)mentioning
confidence: 99%